2015
DOI: 10.1111/jpn.12342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding different levels of corn steep liquor on the performance of fattening lambs

Abstract: This study was conducted to assess the effect of feeding corn steep liquor (CSL) on in vivo digestibility, ruminal pH, ammonia and hydrolytic enzyme activities, blood metabolites, feed intake (FI) and growth performance in fattening lambs. The CSL is a by-product of wet milling process of maize starch industry. The crude protein (CP), rumen-degradable protein (RDP), lactic acid and metabolisable energy contents of this by-product were 420, 324, 200 g/kg dry matter (DM) and 12.6 MJ/kg DM respectively. Twenty-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…However, CSL was used as unconventional animal feed source of energy and / or protein for feeding finishing steers (Trenkle, 2002), lambs (Mirza and Mushtaq, 2006;Freitas et al, 2015;Azizi-Shotorkhoft et al, 2016), Labeo rohita fingerlings and carp (Chovatiya et al, 2010), chicken (Rafhan Product Reference Guide, 2010; Ullah et al, 2017), lactating cows (Santos et al, 2012), crossbred calves (Siverson, 2013), Rahmani lambs (El-Emam et al, 2014), ewes (Hafez et al, 2015;Khalifa et al, 2015b) Zaraibi nanny goats (Khalifa et al, 2015a andSaba et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, CSL was used as unconventional animal feed source of energy and / or protein for feeding finishing steers (Trenkle, 2002), lambs (Mirza and Mushtaq, 2006;Freitas et al, 2015;Azizi-Shotorkhoft et al, 2016), Labeo rohita fingerlings and carp (Chovatiya et al, 2010), chicken (Rafhan Product Reference Guide, 2010; Ullah et al, 2017), lactating cows (Santos et al, 2012), crossbred calves (Siverson, 2013), Rahmani lambs (El-Emam et al, 2014), ewes (Hafez et al, 2015;Khalifa et al, 2015b) Zaraibi nanny goats (Khalifa et al, 2015a andSaba et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CMCase activity was high in HC‐milled and CH‐boiled treatments as compared to the two other treatments. In ruminants, the activity of fibrolytic enzymes as an indicator of fibre digestion (Azizi‐Shotorkhoft, Sharifi, Mirmohammadi, Baluch‐Gharaei, & Rezaei, ) increased when NDF intake was increased (Hristov, McAllister, & Cheng, ). The high activity of CMCase in group CH‐boiled could be explained by the increase in fibre intake and at the same time the decrease in starch entering to the hindgut.…”
Section: Discussionmentioning
confidence: 99%
“…The pancreatic amylase activity has been reported to enhance threefolds in first 10‐day post‐hatch, whereas trypsin and lipase activity would increase fivefold ‐sixfold in the similar period (Nir, Nitsan, & Mahagna, ). Azizi‐Shotorkhoft, Sharifi, Mirmohammadi, Baluch‐Gharaei, and Rezaei () indicated that the effects of CSL on diet digestibility are controversial and might be mainly affected by the total amount of CSL in the diet and by the composition of the diet (interactions of the diet). So, that might be the reason for the different CP digestibilities in the present study.…”
Section: Discussionmentioning
confidence: 99%